Self-harm, capacity, and refusal of treatment: implications for emergency medical practice. A prospective observational study. Issue 11 (21st October 2005) - Jacob, R; Clare, I C H; Holland, A; Watson, P C; Maimaris, C; Gunn, M
Abstract : Objectives: In the context of increasing attention to the rights of adults to make treatment decisions for themselves, this study investigated, among patients who have engaged in self-harm (i) the extent of valid decision making; (ii) the impact of mental disorders; and (iii) the effect of systematically providing relevant clinical information. Design: A prospective observational study. Setting: The emergency department of a large teaching hospital in southeast England. Participants: Seventy one adult men and women who had presented for treatment following self-harm. Main outcome measures: Semi-structured interviews were used to make clinical judgements about participants' capacity to consent before, and following, the presentation of simple written information about the proposed treatment(s). Demographic data, and data about mental disorder and alcohol misuse, were also collected. Results: Based on accepted legal criteria, only 28/71 (39.4%) of the patients were judged to have capacity to consent to the proposed intervention(s) initially. However, the number of patients judged to have capacity improved significantly (p<0.001) after the presentation of written information, to 45/71 (63.4%). Those judged incapable were significantly more likely (p<0.01) to refuse treatment. Continuing incapacity was significantly associated only with cognitive impairment (p<0.001) and/or severe psychiatric disturbance (p<0.01). Conclusions: Consistent with current views, capacity is not static, even among patients who have engaged in self-harm, but can be improved through a simple intervention. The findings are consistent with recent guidance about supporting this vulnerable group of patients, many of whom are ambivalent about treatment.